Recurrent Representation for Non-Stationary Parameter Estimate of Least Squares Method with Least Deviations from "Attraction" Points for Bilinear Dynamic Systems - Слабоспицький, Олександр Сергійович (Київський національний університет імені Тараса Шевченка, 2019)
The estimation problem of non-stationary parameter matrices is considered for bilinear discrete dynamic system in the case when for these unknown parameter matrices their ‘attraction’ points are known at any moment. Explicit and recurrent forms of representation are obtained for these parameter estimates of the least squares method with variable forgetting factor and least deviation norm from ‘attraction’ points under non-classical assumptions. The recurrent algorithm is also proposed for corresponding weighted residual sum of squares.

Рассматривается задача оценивания нестационарных матриц параметров для билинейной дискретной динамической системы в случае, когда для этих неизвестных матриц параметров в каждый момент известны их точки “притяжения". Полученные явная и рекуррентная формы представления для этих оценок параметров метода наименьших квадратов с переменным фактором забывания и наименьшей нормой отклонения от точек “притяжения” при неклассических предположениях. Предложен также рекуррентный алгоритм для соответствующей взвешенной остаточной суммы квадратов.

Розглядається задача оцiнювання нестацiонарних матриць параметрiв для бiлiнiйної дискретної динамiчної системи увипадку, коли для цих невiдомих матриць параметрiв їх точки “тяжiння” вiдомi у кожен момент. Отриманi явна та рекурентна форми представлення для цих оцiнок параметрiв методу найменших квадратiв зi змiнним фактором забування та найменшою нормою вiдхилення вiд точок “тяжiння” при некласичних припущеннях. Запропоновано також рекурентний алгоритм для вiдповiдної зваженої залишкової суми квадратiв.
Рекуррентное представление для оценки нестационарных параметров метода наименьших квадратов с наименьшими отклонениями от точек “притяжения” для билинейных динамических систем
Рекурентне представлення для оцiнки нестацiонарних параметрiв методу найменших квадратiв з найменшими вiдхиленнями вiд точок “тяжiння” для бiлiнiйних динамiчних систем
Keywords: non-stationary parameter estimation; least squares method; ‘attraction’ points; variable forgetting factor; pseudo-inverse operator; recurrent algorithm; bilinear discrete dynamic system; weighted residual sum of squares; оцiнювання нестацiонарних параметрiв; метод найменших квадратiв; точки “тяжiння”; змiнний фактор забування; оператор псевдообернення; рекурентний алгоритм; бiлiнiйна дискретна динамiчна система; зважена залишкова сума квадратiв; оценка нестационарных параметров; метод наименьших квадратов; точки “притяжения”; переменный фактор забывания; оператор псевдообращения; рекуррентный алгоритм; билинейная дискретная динамическая система; взвешенная остаточная сумма квадратов